Resurrecting legal extraterritoriality in occupied Istanbul, 1918–1923. Issue 5 (3rd September 2018) - MacArthur-Seal, Daniel-Joseph
ABSTRACT: The short-lived Allied occupation of Istanbul produced a distinctive blend of legal innovation and revival, creating new mixed courts, reanimating the contested capitulations, and pressuring the Ottoman government to abandon wartime legislation in favour of new laws conducive to European interests. Such measures were intended to serve a military regime notable as much for its disregard for legal procedure when it suited the interests of the occupying Allies as its insistence on protecting the legal privileges of its own subjects. The article shows how the resulting tensions between Britain and the Istanbul and Ankara governments over law and its enforcement furthered the rift between Britain and Turkey until the eventual abandonment of extraterritoriality during the Lausanne conference in 1923.